The syntax of German - Haider, Hubert (Cambridge, UK. : Cambridge University Press, 2010)
'What do you know, if you know that a language has'Object Verb' structure rather than'Verb Object'? Answering this question and many others, this book provides an essential guide to the syntactic structure of German. It examines the systematic differences between German and English, which follow from this basic difference in sentence structure, and presents the main results of syntactic research on German. Topics covered include the strict word order in VO vs word order variation in OV, verb clustering, clause union effects, obligatory functional subject position, and subject-object asymmetries for extractions. Through this, a cross-model and cross-linguistic comparison evolves, highlighting the immediate implications for non-Germanic OV languages, and creating a detailed and comprehensive description of the syntactic differences that immediately follow from an OV type in contrast with a VO type like English. It will be of interest to all those interested in syntax and Germanic languages'--Provided by publisher.
Includes bibliographical references (p. 354-367) and index.
Includes bibliographical references.
Keywords: German language -- Syntax